INFLUENCE OF CUSTOMER EXPERIENCE, CUSTOMER ENGAGEMENT, AND CUSTOMER SATISFACTION TOWARDS CONSUMER LOYALTY OF COSMETIC PRODUCTS GLAD2GLOW AMONG STUDENTS FACULTY ECONOMICS AND BUSINESS UNIVERSITAS OF MALIKUSSALEH - Ainna Mahrum Nasution; Jullimursyida; Mohd. Heikal; Hamdiah (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Consumer loyalty is one of the important factors that determines a company's success in retaining customers amidst increasingly competitive cosmetics industry competition. This study aims to analyze the influence of Customer Experience, Customer Engagement, and Customer Satisfaction on Customer Loyalty toward Glad2Glow cosmetic products among students of the Faculty of Economics and Business, Malikussaleh University. This research was motivated by the increasingly intense competition in the cosmetic industry, requiring companies to create positive customer experiences, strengthen customer engagement, and improve customer satisfaction in order to enhance customer loyalty. This study employed a quantitative approach using a survey method. The population consisted of 3,173 students of the Faculty of Economics and Business, Malikussaleh University who use Glad2Glow cosmetic products. The sampling technique used was purposive sampling, resulting in 112 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the Statistical Product and Service Solutions (SPSS) program. The findings reveal that Customer Experience has a positive and significant effect on Customer Loyalty, Customer Engagement has no significant effect on Customer Loyalty, while Customer Satisfaction has a positive and significant effect on Customer Loyalty. The coefficient of determination (Adjusted R Square) of 55.9% indicates that Customer Experience, Customer Engagement, and Customer Satisfaction explain 55.9% of the variation in Customer Loyalty, while the remaining 44.1% is explained by other variables outside the scope of this study. Therefore, improving customer experience and customer satisfaction is essential to strengthening customer loyalty toward Glad2Glow cosmetic products.